Rancang Bangun Pendidikan Multikultural Berdasarkan Kajian Teologi “Berbuat Baik” Menurut Perjanjian Lama - GP, Harianto (Basileus Eirene: Jurnal Agama dan Pendidikan, 2022)
Doing good is universal in which all people with various religious, ethnic and other backgrounds are certainly happy to do good. The problems that arise in the following questions are: What are the values of doing good according to the Bible? What is the challenge of "doing good" according to the dimensions of Multicultural Theology? How is the implementation of Multicultural Theology education about doing good into Christian ministry? The answer is: (1) Good deeds are commands given by God to His people. If a human being wants to be said to be good, he is obliged to do good. Because good deeds have a universal character. (2) The challenge of “doing good” in the dimension of multicultural theology is: the challenge of “doing good” in theocentric, the challenge of “doing good” in Christocentric (the principle of the Incarnation, the principle of salvation, the principle of the Holy Spirit, and the principle of the Naturality of the Church) and (3) the challenge "Doing Good" from Theocentric to Christocentric". Multicultural theology regarding "doing good" becomes a very influential implementation to lead someone to enter the concept of theocracy which is then sharpened to Christocentric. Here the value of the Great Commission of Jesus Christ to win people becomes real and can be implemented properly. But, of course, the work of the Holy Spirit in the believer is critical to the success of the Great Commission mission.